Water Soluble Coumarin Quaternary Ammonium Chlorides: Synthesis and Biological Evaluation - Karatas, Mert O.; Noma, Samir A. A.; Gurses, Canbolat; Balcioglu, Sevgi; Ates, Burhan; Alici, Bulent; Cakir, Umit (Wiley-V C H Verlag Gmbh, 2020)
In the present study, coumarin-bearing three pyridinium and three tetra-alkyl ammonium salts were synthesized. The compounds were fully characterized by(1)H- and(13)C-NMR, LC/MS and IR spectroscopic methods and elemental analyses. The cytotoxic properties of all compounds were tested against human liver cancer (HepG2), human colorectal cancer (Caco-2) and non-cancer mouse fibroblast (L-929) cell lines. Some compounds performed comparable cytotoxicity with standard drug cisplatin. Antibacterial properties of the compounds were tested against Gram-negativeEscherichia coliand Gram-positiveBacillus subtilisbacteria, but the compounds did not have any antibacterial effect against both bacteria. Enzyme inhibitory properties of all compounds were tested on the activities of human carbonic anhydrase I and II, and xanthine oxidase. All compounds inhibited both enzymes more effectively than standard drugs, acetazolamide and allopurinol, respectively. The biological evaluation results showed that ionic and water soluble coumarin derivatives are promising structures for further investigations especially on enzyme inhibition field.
Keywords: coumarin; cytotoxicity; antimicrobial activity; enzyme inhibition